Brain natriuretic peptide modulates calcium homeostasis and epidermal growth factor receptor gene signalling in asthmatic airways smooth muscle cells. (April 2015) - Orlandi, Augusto; Calzetta, Luigino; Doldo, Elena; Tarquini, Chiara; Matera, Maria Gabriella; Passeri, Daniela
Abstract: The airway epithelium acts as a barrier and provides a critical interface between the body and the external environment. Brain natriuretic peptide (BNP) plays an important role in several bronchial functions, including relaxation. BNP relaxes airways by binding and activating natriuretic peptide receptor-A expressed from the airway epithelium. Although relaxation effect has been extensively investigated, less is known about BNP-regulated intracellular biomolecular pathways leading to bronchial relaxation. To this aim, we investigated BNP effects on gene signalling of airway smooth muscle cells (ASM) obtained from donors with asthma by using a RT 2 profiler™ PCR array. When compared with control, treatment for 2 h with supernatant from BNP-treated (1 μM) bronchial epithelial cells (BEAS-2B) induced in asthmatic ASM cells a rapid reduction of transcription of EGFR and genes involving in actin and calcium homeostasis, as those of Protein kinase C (PKC) and RhoA-ROCK gene pathways. Immunofluorescence and western blotting did not shown any difference comparing control and ASM cells treated with conditioned medium from BNP-treated BEAS-2B. This study provides evidence that the effect of BNP on relaxing bronchial in ASM cells is mediated from epithelium and associates to rapid changes of EGFR and calcium homeostasis-associated gene levels.